(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Solovyova N. D., Sorochan L. F. Improving English language lessons. On the base of analysis of teachers’ common mistakes during English lessons recommendations to improve the effectiveness of lessons are given in the article.